Pengaruh Proses Biodrying dalam Pemanfaatan Biomasa menjadi Solid Recovery Fuel (SRF) - Darojat, Khumaidah; Yusrina, Afifah; Ardhianto, Rachmad; Hendri (Al-Ard: Jurnal Teknik Lingkungan, 2024)
In developing countries, municipal solid waste remains a major unresolved problem. One way to manage municipal solid waste is to produce biomass. Biomass management from solid waste involves a natural or mechanically assisted biological drying process using bulking agents. This study employed natural and mechanical biodrying systems with blower assistance and corn starch industrial wastewater bulking agents. A blower expedites the process of reducing waste weight. The reactor with the blower exhibited the largest decrease in water content under the bulking agent addition conditions when the water content fell below 15%. Using a blower in the biodrying process reduces the drying time of biomass raw material by 50% compared to the non-blower method, which takes up to 12 days. 1 L of the bulking agent is the most effective biodrying dose. The percentage carbon value in the biodrying process was 42.02% higher when a bulking agent was used than a non-bulking agent (35.98%) and a blower was not used (40.82%). Including a bulking agent during biodrying enhances the composition's elemental value and speeds up the reduction and evaporation or drying of waste.